2013
DOI: 10.15376/biores.8.2.2246-2256
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Chemical Composition of Cork

Abstract: The chemical composition of cork was determined, following a sampling that covered the whole production area in Portugal (29 provenances from six regions) with samples taken at cork stripping. To analyse between population variations, a more intensive sampling was made in two locations. The overall mean chemical composition of cork was: extractives 16.2% (dichloromethane 5.8%, ethanol 5.9%, water 4.5%), suberin 42.8% (long-chain lipids 41.0%, glycerol 3.8%), and lignin 22.0% (Klason 21.1%, acid soluble 0.9%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
91
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 7 publications
14
91
1
Order By: Relevance
“…Table 1 presents the chemical characterization of the cork sample used in this work. The extractive percentage (14.1) was comparable to the average percentage reported by Pereira (2013). There was a similar percentage of water and ethanol extracts, higher than dichloromethane.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)supporting
confidence: 75%
See 2 more Smart Citations
“…Table 1 presents the chemical characterization of the cork sample used in this work. The extractive percentage (14.1) was comparable to the average percentage reported by Pereira (2013). There was a similar percentage of water and ethanol extracts, higher than dichloromethane.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)supporting
confidence: 75%
“…There was a similar percentage of water and ethanol extracts, higher than dichloromethane. The suberin content was smaller than the average (42.8%) reported by Pereira (2013). Nevertheless, it was clearly in the interval reported (23.1 to 54.2%).…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)contrasting
confidence: 63%
See 1 more Smart Citation
“…In studies with eucalyptus, a strong positive correlation between the pulp yield and cellulose content and negative correlation with lignin content have been observed. Pereira (1988) observed variability in chemical composition, mainly for pulp content, between trees of Eucalyptus globulos in the same location and different geographic locations, a fact that corroborates the differences in the profile of proteins found among clones of this study.…”
Section: Proteomic Characterization Of Eucalyptus Clonessupporting
confidence: 88%
“…It is known that such amplitude of values is due to different factors such as wood origin (Miranda and Pereira 2002b;Poke et al 2006) or age of the tree (Miranda and Pereira 2002c). The values of soluble lignin observed for wood material (3.9% and 4.0%, Table 1) are comparable with the reported 3.6% (Pereira 1988) and are in the range of 4.4% to 8.1% (Poke et al 2006). The values of Klason lignin (21.4 % and 21.8 %) were observed to be in the range of 18.9% to 25.5% reported by Poke et al (2006) and near the reported 19.8% (Rencoret et al 2011).…”
Section: Lignin Determination By Wet Chemistrysupporting
confidence: 80%